2021
DOI: 10.1080/10717544.2021.1943060
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of injectable hydrogels associate with Adipose-Derived stem cells delivery for anti-cardiac hypertrophy agents

Abstract: Adipose-derived stem cells (ADSCs) treatment offers support to new methods of transporting baseline cell protein endothelial cells in alginate (A)/silk sericin (SS) lamellar-coated antioxidant system (ASS@L) to promote acute myocardial infarction. In the synthesized frames of ASS, the ratio of fixity modules, pores, the absorption and inflammation was detected at ka (65ka), 151 ± 40.12 lm, 92.8%, 43.2 ± 2.58 and 30.10 ± 2.1. In this context, ADSC-ASS@L was developed and the corresponding material was stable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Encapsulated hiPSCs within a hydrogel, which has demonstrated promise in cardiac differentiation, indicated a promising future for regenerative therapies . Another work utilized a novel hydrogel system to encapsulate adipose-derived stem cells, resulting in positive outcomes for the treatment of cardiac damage following heart attacks . Simultaneously, in a recent research, a 3D cardiac mesh tissue that has demonstrated efficacy in preserving cell health and enhancing cardiac function in rats was developed .…”
Section: Evs-loaded Hydrogels: a Promising Approach For Tissue Regene...mentioning
confidence: 99%
See 1 more Smart Citation
“…Encapsulated hiPSCs within a hydrogel, which has demonstrated promise in cardiac differentiation, indicated a promising future for regenerative therapies . Another work utilized a novel hydrogel system to encapsulate adipose-derived stem cells, resulting in positive outcomes for the treatment of cardiac damage following heart attacks . Simultaneously, in a recent research, a 3D cardiac mesh tissue that has demonstrated efficacy in preserving cell health and enhancing cardiac function in rats was developed .…”
Section: Evs-loaded Hydrogels: a Promising Approach For Tissue Regene...mentioning
confidence: 99%
“…202 Another work utilized a novel hydrogel system to encapsulate adipose-derived stem cells, resulting in positive outcomes for the treatment of cardiac damage following heart attacks. 203 Simultaneously, in a recent research, a 3D cardiac mesh tissue that has demonstrated efficacy in preserving cell health and enhancing cardiac function in rats was developed. 204 Additionally, silk fibroin has been lauded for its ability to induce pacemaker cells to resemble authentic sinoatrial-node cardiomyocytes.…”
Section: Hydrogels: Synthesis Classifications Primary Biomedical Appl...mentioning
confidence: 99%
“…ADSCs within an alginate (A)/silk sericin lamellar-coated system showed efficiency in acute MI and coronary artery hypertrophy. 171 Another ADSC-loaded hydrogel with a controllable H 2 Sreleasing behavior and conductivity could adapt to and ameliorate the MI condition, thereby improving retention of ADSCs in the infarcted region. 40 With a certain number of viable ADSCs retained inside, PEG hydrogels promoted ADSCs to secret VEGF for cardiac recovery post-MI.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…[56] The field of regenerative medicine has proposed strategies for biomimetic carriers. To date, there are many forms of cell carriers, including patches, [7,36,57,58] particles, [49,[59][60][61] hydrogels, [62][63][64][65] electro-discharge nanofibers, [21,33,[66][67][68] sprays, [6] etc. On the one hand, the delivery of cells through biomaterial carriers can reduce microenvironmental shocks and promote cell survival and retention.…”
Section: Introductionmentioning
confidence: 99%